Comparison of approaches to determine echocardiographic outcomes for children with latent rheumatic heart disease. Issue 2 (1st December 2022) - Rwebembera, Joselyn; Beaton, Andrea; Okello, Emmy; Engelman, Daniel; Fall, Ndate; Mirabel, Mariana; Nakitto, Miriam; Pereira Nunes, Maria Carmo; Pulle, Jafesi; Sarnacki, Rachel; Scheel, Amy; Zuhlke, Liesl; et al.
Abstract : Background: Screening programmes using echocardiography offer opportunity for intervention through identification and treatment of early (latent) rheumatic heart disease (RHD). We aimed to compare two methods for classifying progression or regression of latent RHD: serial review method and blinded, side-by-side review. Methods: A four-member expert panel reviewed 799 enrolment (in 2018) and completion (in 2020) echocardiograms from the GOAL Trial of latent RHD in Uganda to make consensus determination of normal, borderline RHD or definite RHD. Serial interpretations (enrolment and completion echocardiograms read at two different time points, 2 years apart, not beside one another) were compared with blinded side-by-side comparisons (enrolment and completion echocardiograms displayed beside one another in random order on same screen) to determine outcomes according to prespecified definitions of disease progression (worsening), regression (improving) or no change. We calculated inter-rater agreement using Cohen's kappa. Results: There were 799 pairs of echocardiogram assessments included. A higher number, 54 vs 38 (6.8% vs 4.5%), were deemed as progression by serial interpretation compared with side-by-side comparison. There was good inter-rater agreement between the serial interpretation and side-by-side comparison methods (kappa 0.89). Disagreement was most often a result of the difference in classification between borderline RHD and mild definite RHD. Most discrepancies between interpretation methods (46 of 47, 98%) resulted from differences in valvular morphological evaluation, with valves judged to be morphologically similar between enrolment and final echocardiograms when compared side by side but classified differently on serial interpretation. Conclusions: There was good agreement between the methods of serial and side-by-side interpretation of echocardiograms for change over time, using the World Heart Federation criteria. Side-by-side interpretation has higher specificity for change, with fewer differences in the interpretation of valvular morphology, as compared with serial interpretation.